Mujahid's biography in seeking knowledge and spreading it (Journal of the College of Basic Education, 2023)
My talk to you this time, O flowers of hope; the fragrance of wishes; O people of the present and heroesthe recipient; O happiness of homes; And the joy of souls, O adornment of worldly life, for a wonderful socket of masterpiecesour bright old glory; Like Sami, our generous Arab land gives birth to him. Holy landmiracles; the land of the prophets, the saints and the righteous; the land of knights, scholars, and virtuous men; inEvery part of it is in its mountains, valleys, plains, plateaus, beaches, islands and deserts.And its valleys...the land of figs, olives, palm trees and pomegranates...the land of horses, camels and falconsAnd doves.... the land of oil, gas, coral, pearls and gold... the land of goodness in all its colorsand its varieties; and countless blessings....the land of rare heroics in opinion and courageWisdom, leadership, leadership, equestrian, science, literature, culture, arts and spotless talentsthat never runs out..In the heights of the northern shores of the Arabian Gulf.... where the land of Mesopotamia flows smoothlyThe waters of the Tigris and Euphrates.. A large fresh water artery descends from the beginning of its formation. from confluencethe Tigris and Euphrates rivers in one watercourse; Its name is Shatt al-Arab; near the area calledhorn It is 181 km away from the northern shores of the Arabian Gulf, and this number represents the length of this riverIts width is from the beginning of its formation at the century of 005 AD, and at its mouth in the Arabian GulfM, which increases the splendor and beauty of the Shatt al-Arab, the spread of palm groves, fruits and water-wheelsand the rivers on its banks; And swamps and marshes in the north at the end of the Mesopotamian plainsedimentary and scattered in the waters of the Shatt al-Arab and the swamps near it many islands.